Cultural options of transatlantic exile: Rosalía de Castro’s image as conjured up by Galician Day commemorations on the two shores - Jones, Irene (2021)
This paper examines the 1950 commemoration of Galician Day held in Argentina and Spain, and the symbolic significance it acquires in these two countries, which were undergoing different political circumstances. While the Buenos Aires celebration is inspired in the topic of exile following the Francoist dictatorship, in Santiago de Compostela stands out the liturgical and religious content surrounding the exaltation of Saint James the Great, and draws upon the existing allegiance of the Catholic Church to the Francoist regime. In this context, we will dig into the symbolic identity of the poet Rosalía de Castro along both commemorations, the symbols her figure was associated to and the enshrinement she was submitted to. Our work will be informed by the Galicia magazine — Centro Gallego de Buenos Aires house organ — and El Correo Gallego and La Noche dailies, from Santiago de Compostela, as well as the correspondence that Luis Seoane, an exiled intellectual in Buenos Aires, exchanged with some of the contributors of each paper.